Rapid subtyping of tick-borne encephalitis virus isolates using multiplex RT-PCR - Růzek, Daniel; Stastná, Hana; Kopecký, Jan; Golovljova, Irina; Grubhoffer, Libor (Journal of virological methods, 2007)
Tick-borne encephalitis virus, an emerging pathogen in several countries in Europe and Asia, has been divided into three subtypes (European, Siberian and Far Eastern). These subtypes are associated with different severities of the disease. For that reason, early determination of the subtype in a clinical sample or in ticks removed from a patient in areas of co-circulation of two or three subtypes is of high importance. The development of a simple method of multiplex RT-PCR for rapid and easy subtyping of tick-borne encephalitis virus isolates is reported to fill this requirement. The method is based on the unique combination of oligonucleotide primers hybridizing with subtype-specific "signature" positions of the sequence encoding the viral envelope protein. The developed multiplex RT-PCR also appears to be a useful method in studies focused on the molecular-epidemiology of tick-borne encephalitis virus.
Keywords: viry klíšťové encefalitidy; Encephalitis Viruses, Tick-Borne; RNA, Viral; RNA virová; Ticks; Molecular Epidemiology; polymerázová řetězová reakce s reverzní transkripcí; senzitivita a specificita; Animals; Sensitivity and Specificity; Humans; lidé; klíšťata; Reverse Transcriptase Polymerase Chain Reaction; zvířata; Encephalitis, Tick-Borne; klíšťová encefalitida; molekulární epidemiologie